Chirp-coded excitation imaging with a high-frequency ultrasound annular array - Mamou, Jonathan; Ketterling, Jeffrey A.; Silverman, Ronald H. (IEEE transactions on ultrasonics, ferroelectrics, and frequency control, 2008)
High-frequency ultrasound (HFU, > 15 MHz) is an effective means of obtaining fine-resolution images of biological tissues for applications such as opthalmologic, dermatologic, and small animal imaging. HFU has two inherent drawbacks. First, HFU images have a limited depth of field (DOF) because of the short wavelength and the low fixed F-number of conventional HFU transducers. Second, HFU can be used to image only a few millimeters deep into a tissue because attenuation increases with frequency. In this study, a five-element annular array was used in conjunction with a synthetic-focusing algorithm to extend the DOF. The annular array had an aperture of 10 mm, a focal length of 31 mm, and a center frequency of 17 MHz. To increase penetration depth, 8-mus, chirp-coded signals were designed, input into an arbitrary waveform generator, and used to excite each array element. After data acquisition, the received signals were linearly filtered to restore axial resolution and increase the SNR. To compare the chirp-coded imaging method with conventional impulse imaging in terms of resolution, a 25-mum diameter wire was scanned and the -6-dB axial and lateral resolutions were computed at depths ranging from 20.5 to 40.5 mm. The results demonstrated that chirp-coded excitation did not degrade axial or lateral resolution. A tissue-mimicking phantom containing 10-mum glass beads was scanned, and backscattered signals were analyzed to evaluate SNR and penetration depth. Finally, ex vivo ophthalmic images were formed and chirp-coded images showed features that were not visible in conventional impulse images.